Innovation Diffusion in the Sustainable Design of Sport Venues - Timothy Kellison; Sungil Hong (Journal of Applied Sports Management, 2023)
Herein, the authors contribute to the sport facilities literatures by discussing the current state of innovation diffusion in sustainable design among sport’s professional arenas, ballparks, and stadiums. Diffusion of innovation theory is reviewed before the authors explore how this theory can be applied to sport facility design and operation.
Keywords: Facility Design; Operation Management; Sport Facilities; Sustainability